Mitigating CO2 Leakage by Immobilizing CO2 into Solid Reaction Products. (July 2017) - Wasch, Laura J.; Wollenweber, Jens; Neele, Filip; Fleury, Marc
Abstract: In the unlikely case of CO2 leakage from a storage reservoir, it is desirable to close the leak efficiently and permanently. This could be done by injecting a reactive solution into the leak path, thereby immobilizing migrating CO2 by consuming the gas and forming solid reactants. With regard to permanent closure, it is important to consider materials that are stable in the long-term, ensuring permanent CO2 containment. Numerical modelling was applied to assess the feasibility of injecting calcium-rich water as a CO2 -reactive solution to form calcite. A scenarios analyses of key parameters showed that the success of leakage remediation can be up to 95% when carefully balancing the injection rate and distance versus the permeability and leakage rate.